2018
DOI: 10.3126/ojn.v7i2.20159
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic Index among Nepalese Medical Students

Abstract: Introduction: Cephalic index is race and sex specific parameter. Morphology of all living beings undergoes changes in varying degrees during their life and the features are variable in the individuals of the same species.Objective: To measure the head size of the Nepalese medical students of both sexes between 18 to 24 years of age, to determine the different head type and to explore the distribution of cephalic index by ethnicity.Materials & Method: Materials used were a Spreading caliper and a measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In contrast to this finding, other studies performed in Nepal revealed statistically significant value of cephalic index between male and female. 11,14 In this study, it was observed that dolichocephaly was the most common head type. This finding is consistent with findings of other studies performed in Croatia and Nigeria.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In contrast to this finding, other studies performed in Nepal revealed statistically significant value of cephalic index between male and female. 11,14 In this study, it was observed that dolichocephaly was the most common head type. This finding is consistent with findings of other studies performed in Croatia and Nigeria.…”
Section: Discussionmentioning
confidence: 70%
“…8,12 On the contrary, brachycephaly was reported as most common head type in other studies conducted in Nepal and in another study conducted in India, brachycephaly and dolichocephaly were equally frequent (33%) followed by mesocephaly (27%). 11,13,14 On the other hand, in other studies conducted in parts of India, most common head type reported was mesocephalic type. 9,10 Many researchers have raised the topic of "brachycephalisation" in their studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…10 In contrast it was recorded as the least common type among Nepalese Medical students of all the three ethnic groups namely Brahmin, Newar and Chettri. 26 It was the least common among (4.32%) Thai 24 and Japanese populations as well. 3 A study done among Colombian population found that the mesocephalic was the second common type of head 27 which was comparable to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was recorded the most common type among Brahmin, Newar and Chettri of Nepalese population. 26 It was also the most common among Albanians of Kosovo 16 and Srilankan population. 32 The present study did not record hyperbrachycephalic type of head which was similar to the study done by Setiya et al 31 So it is obvious that hereditary factor is primarily responsible for this variability in head shape in various ancestries, ethnicities and geographical regions, however environment has secondary effect on it.…”
Section: Discussionmentioning
confidence: 99%